The positive case for a CBDC - Andrew Usher; Edona Reshidi; Francisco Rivadeneyra; Scott Hendry (Bank of Canada, 2021)
In this paper we discuss the competition and innovation arguments for issuing a central bank digital currency (CBDC). A CBDC could be an effective competition policy tool for payments. On innovation, we argue that a CBDC could be necessary to support the vibrancy of the digital economy by helping solve market failures and fostering competition and innovation in new digital payments markets. Overall, competition and innovation are supporting arguments for issuing a CBDC.
Keywords: E42; E58; L4; L5; 330; Digital currencies and fintech; Financial institutions; Financial stability